SKRINING ONIKOMIKOSIS PADA PETUGAS SAMPAH - Farizah Fahmi, Norma; Thuti' Nashiha, Aluf (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
Onychomycosis is a fungal infection of the nail plate caused by dermatophyte, non-dermatophyte and yeast fungi. Onychomycosis causes damage to the nails, causing them to become thickened, brittle and easily destroyed. The factor causing nails to be infected with fungus is frequent direct contact with a humid and dirty environment. The purpose of this study was to determine the presence of Trichophyton sp., Aspergillus sp., Candida albicans fungal infections in the nails of waste officers at the Bangkalan District Environmental Service.The research method used was descriptive and the research design used cross-sectional. The variables in this study were nail fungus in waste officers. The samples used were 46 samples from a total population of 91 respondents. This research was conducted at the Microbiology Laboratory of STIIKes Ngudia Husada Madura.The results obtained from this study with a total sample of 46 showed that nails were infected with Trichophyton sp., totaling 3 samples with a percentage of 9%, Aspergilus sp. as many as 10 samples with a percentage of 29% and Candida albicans 0%. Factors that cause fungal infections in nails are frequent contact with humid and dirty environments, not washing hands and feet using personal protective equipment while working. The results of this study found Trichophyton sp. and Aspergillus sp. fungi on the nails of garbage officers at the Bangkalan District Environmental Service. Prevention of nail infections in garbage officers can be done by using personal protective equipment (PPE) while working, washing hands and feet with soap.